2021
DOI: 10.7759/cureus.20431
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Low Serum Vitamin D Levels in Patients Presenting With Androgenetic Alopecia: A Review

Abstract: The role of vitamin D receptor (VDR) has been well established and extensively studied in the hair cycle. Its deficiency is also closely linked to several types of alopecia, including alopecia areata, telogen effluvium, and androgenetic alopecia (AGA). Since there is limited research on the correlation between androgenetic alopecia and low serum vitamin D levels, our review aims to find relevant articles and comprehensively present them. A review of the literature was performed to gain insight into AGA. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…However, hair thickness is determined by the size of the hair follicle, 16 and the anagen phase lasts for 4-7 years. 17 Hence, even when HRT was assumed to affect hair thickness, observing large-scale changes that affect the mean value over a 6-month study period may be difficult. Triglyceride levels are increased by HRT, 12 and in this study, while no statistically significant differences were noted, an increasing trend was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hair thickness is determined by the size of the hair follicle, 16 and the anagen phase lasts for 4-7 years. 17 Hence, even when HRT was assumed to affect hair thickness, observing large-scale changes that affect the mean value over a 6-month study period may be difficult. Triglyceride levels are increased by HRT, 12 and in this study, while no statistically significant differences were noted, an increasing trend was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, hair thickness is determined by the size of the hair follicle, 16 and the anagen phase lasts for 4–7 years. 17 Hence, even when HRT was assumed to affect hair thickness, observing large-scale changes that affect the mean value over a 6-month study period may be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the existing literature and the hypotheses we formulated when designing our study, vitamin D may affect the development of AGA through both direct and indirect mechanisms. 17 The direct mechanisms in which vitamin D may affect AGA development is through its high expression in the hair follicle stem cells and the involvement of vitamin D receptor (VDR) in regulating hair cycling in all but the first phase. In VDR knockout mice, hair follicle stem cells are reduced and their activity is weakened, resulting in hair loss.…”
Section: Discussionmentioning
confidence: 99%
“…Data is scarce regarding the efficacy of vitamin D supplementation or topical solution for patients with vitamin D deficiency and concomitant alopecia. However, animal model studies have found benefit with vitamin D supplementation [69], and oral vitamin D supplementation with minoxidil was found to be significantly more effective than minoxidil alone in the treatment of FPAnA [70]. Yet, oral vitamin D monotherapy did not result in significant improvement.…”
Section: Vitamin Dmentioning
confidence: 96%